Circadian rhythm in mammals: time to eat & time to sleep. Issue 2 (4th March 2017) - Güldür, Tayfun; Otlu, Hüsniye Gül
Abstract: Circadian rhythm is defined as rhythmic fluctuations in physiological processes which enable living organisms to make necessary arrangements for upcoming changes in the environment thereby optimizing their metabolism. Mammalian circadian clock consists of feedback(negative) and feedforward (positive) loops consisting of transcription, translation and posttranslational events. It is believed that there are two kinds of clock functioning in the body.The master clock residing in hypothalamus oscillating in conjunction with light/dark cycle whereas peripheral clocks occur in peripheral tissues and influenced by other environmental factors such as feeding. The rhythmic alterations in activities of metabolic pathways are provided by the coordinated expressions of clock genes and consequently by clock-controlled genes. The current studies indicate that consumption of food at inappropriate times as well as sleep restrictions lead to metabolic dysfunctions due to disruption of circadian rhythm which result in diabetes, obesity and heart diseases. To this end, it is aimed, in this review, to examine interactions among food or sleep, metabolism and circadian rhythm with an insight into metabolomic profiling studies of circadian disturbances by sleep restrictions following an overview of working mechanisms of circadian rhythms in mammals.